Spatial Distribution Pattern of Hypertension: Case of Jakarta, Indonesia - Martya Rahmaniati Makful; Yohana Septianty Isabel; Verry Adrian (Faculty of Geography, Universitas Gadjah Mada, 2023)
Hypertension is one type of Non-communicable Disease (NCD) that is a burden on the government in disease control every year. Hypertension is caused by various risk factors. Most of the risk factors for hypertension are lifestyles that can be changed. This study aims to determine the pattern of distribution of hypertension cases based on risk factors, social factors, health care facilities. The spatial approach was used to determine the spatial relationship between hypertension risk factors and hypertension cases in the Jakarta province. The spatial approach was used to determine the spatial relationship between hypertension risk factors and hypertension cases in the Jakarta province. The results showed that the screening program variable had a spreading pattern with a negative spatial relationship and there was a spatial interaction between the screening program variables and hypertension cases. Improving the quality and quantity of Non-communicable Disease Integrated Assistance Post activities of local health centers, which are the front line in preventive and promotive activities is expected to be the key to successful control of hypertension cases in the Jakarta.